Exploring the Relation Between Lifestyle Choices and the Occurrence of Colorectal Cancer Disease - E Alabd, Ruaa; Mohsin, Forat Yahya; Oufi, Hayder; Ibrahim, Besmah M. Ali (International Journal of Innovative Research in Medical Science, 2024)
Colorectal cancer is among the leading causes of cancer mortality worldwide. The occurrence of CRC has been associated with various lifestyle risk behaviors about major modifiable risk factors, which include dietary patterns, physical activity, smoking status, and alcohol intake. This study aimed to investigate the association of these parameters of lifestyle with the incidence of CRC. In this case-control study, a total of 140 individuals were enrolled: 70 subjects diagnosed with CRC and 70 controls (1st degree relative). The data were obtained by structured questionnaires and medical records, and analyzed by chi-square tests and logistic regression methods. The results indicated that, compared with their counterparts, physical inactivity, low exercise, smoking, and alcohol drinking are significantly associated with an increased risk for CRC. Besides, other dietary habits, such as high consumption of processed meat and low intake of vegetables and fruits, were major characteristics of the cases of CRC. It has been estimated that promoting healthy lifestyle choices could reduce excess CRC risk by more than 70%. This study underscores the critical role of lifestyle modifications in preventing CRC.